2020
DOI: 10.1111/nmo.14045
|View full text |Cite
|
Sign up to set email alerts
|

Severe gastroparesis is associated with an increased incidence of slow‐transit constipation as measured by wireless motility capsule

Abstract: Background: Dysmotility in one region of the gastrointestinal tract has been found to predispose patients to developing motility disorders in other gastrointestinal segments. However, few studies have evaluated the relationship between gastroparesis and constipation.Methods: Retrospective review of 224 patients who completed 4-hour, solid-phase gastric emptying scintigraphy (GES), and wireless motility capsule (WMC) testing to evaluate for gastroparesis and slow-transit constipation, respectively. When availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…It should be noted that the items in the Diarrhea Scale may also be measuring constipation with overflow fecal incontinence as previously reported (17). Though the pathophysiologic association between gastroparesis and constipation has not been fully elucidated, these findings regarding elevated constipation symptoms in pediatric patients with gastroparesis are consistent with recent findings in adults with gastroparesis (42,43). Our results appear to support the findings in adults that there is significant overlap in symptoms between pediatric patients with gastroparesis and those with gastroparesis‐like symptoms but normal gastric emptying; implying a spectrum of disease rather than two separate disorders (41).…”
Section: Discussionsupporting
confidence: 89%
“…It should be noted that the items in the Diarrhea Scale may also be measuring constipation with overflow fecal incontinence as previously reported (17). Though the pathophysiologic association between gastroparesis and constipation has not been fully elucidated, these findings regarding elevated constipation symptoms in pediatric patients with gastroparesis are consistent with recent findings in adults with gastroparesis (42,43). Our results appear to support the findings in adults that there is significant overlap in symptoms between pediatric patients with gastroparesis and those with gastroparesis‐like symptoms but normal gastric emptying; implying a spectrum of disease rather than two separate disorders (41).…”
Section: Discussionsupporting
confidence: 89%
“…Recent findings with adult patients have demonstrated significant symptoms overlap between gastroparesis and functional dyspepsia, suggesting a spectrum of disease rather than 2 separate disorders (6). The exception to this symptoms overlap is the finding that elevated constipation symptoms are present in adult patients with gastroparesis compared to those with functional dyspepsia (7,8). Notably, we also found in the present study that pediatric patients with gastroparesis reported significantly worse constipation symptoms than pediatric patients with functional dyspepsia.…”
Section: Discussionmentioning
confidence: 99%
“…In adults with gastroparesis, the patient‐reported gastrointestinal symptoms profile is similar to those of adult patients with functional dyspepsia with normal gastric emptying (4–6), except for more constipation symptoms in adult patients with gastroparesis compared to those with functional dyspepsia (7,8). Similarly, when comparing the gastrointestinal symptoms profiles of pediatric patients with gastroparesis to pediatric patients with gastroparesis‐like symptoms with normal gastric emptying, worse constipation and diarrhea/overflow fecal incontinence symptoms were reported by pediatric patients with gastroparesis using the PedsQL Gastrointestinal Symptoms Scales (9).…”
mentioning
confidence: 82%
“…In GESc, a gamma camera is used to detect the migration of radioisotopes, thereby reflecting the transport characteristics of substances in the gastrointestinal tract [ 44 ]. The use of GESc for the investigation of gastroparesis patients was first proposed in 1966 [ 45 ].…”
Section: Discussionmentioning
confidence: 99%